The new ALEPH Silicon Vertex Detector - CREANZA, D. (Institutional Knowledge at Singapore Management University, 1998)
The ALEPH collaboration, in view of the importance of effective vertex detection for the Higgs boson search at LEP 2, decided to upgrade the previous vertex detector. Main changes were an increased length (+/- 20 cm), a higher granularity for r phi view (50 mu m), a new preamplifier (MX7 rad hard chip), a polymide (upilex) fan-out on z side to carry the signals from the strips to the front-end electronics outside the fiducial region reducing consequently the passive material in the central region by a factor of two. The detector, the running experience and its performance will be described. (C) 1998 Elsevier Science B.V. All rights reserved.